S17 Cardiovascular Risk Factors In People With Bronchiectasis: A Cross Sectional Study. (10th November 2014) - Navaratnam, V; Millett, E; Hurst, JR; Thomas, SL; Smeeth, L; Hubbard, RB; Brown, J; Quint, JK
Abstract : Background: We have previously demonstrated that individuals with bronchiectasis have a higher prevalence of cardiovascular disease compared to the general population. 1 It is unclear if this is due higher prevalence of cardiovascular risk factors amongst people with bronchiectasis or through other mechanisms. Methods: We conducted a cross-sectional study using electronic primary care data from the Clinical Practice Research Database (CPRD-GOLD) to estimate the prevalence of cardiovascular risk factors (smoking habit, diabetes, hypertension, hyperlipidaemia, family history of cardiovascular disease) and medication commonly prescribed to manage cardiovascular disease amongst people with and without bronchiectasis. Logistic regression was used to generate odds ratios for each risk factor or cardiovascular drug, adjusting for age and sex. Results: Approximately 3.9 million individuals were included in our study, 10, 942 (0.3%) of which had a record of bronchiectasis. Individuals with bronchiectasis were predominantly female (60.4%) and the median age at time of diagnosis was 56.2 (Interquartile range: 40.6–67.5) years. The prevalence of hypertension, diabetes and hypercholesterolaemia was slightly lower in individuals with bronchiectasis. We also found that people with bronchiectasis were less likely to have prescriptions for beta blockers, angiotensin converting enzyme inhibitors or angiotensin II receptor blockers, anti-platelets and lipid lowering drugs (see Table 1 ). Conclusions: Patients with bronchiectasis have a lower prevalence of cardiovascular risk factors compared to the general population. This raises the possibility that other factors associated with bronchiectasis could be contributing to the increase risk in cardiovascular disease. Reference: Navaratnam V, Millett E, Hurst JR, Thomas S, Smeeth L, Hubbard R, Brown JS, Quint JK. The association between bronchiectasis and cardiovascular disease: A population based study. American Journal of Respiratory and Critical Care Medicine 2014; 189:A3618